Accounts on Liabilities and Methodological Approaches to Their Analysis - Murodovich, Gaybullaev Rakhim; Hassan, Anvarov (Research Parks Publishers, 2023)
In this article, the emergence of obligations in the accounting of business entities, the income and expenses reflected in the accounting accounts as obligations that change the financial result of the economic activity of the organization, and the specific aspects of their emergence are revealed. Within the scope of the topic, the researches of economists were researched and conclusions and suggestions were given on the topic.